2007
DOI: 10.1021/la702837j
|View full text |Cite
|
Sign up to set email alerts
|

Porous Conducting Polymer/Heteropolyoxometalate Hybrid Material for Electrochemical Supercapacitor Applications

Abstract: A porous conducting polymer/heteropolyoxometalate hybrid material that displays high specific capacitance and low ionic resistance has been prepared for electrochemical supercapacitor applications. Polypyrrole/phosphomolybdate composite films were chemically synthesized in tetrahydrofuran in the presence of sodium sulfate, which acts as a porogen. While the phosphomolydic acid could be removed from the film upon rinsing with pure tetrahydrofuran or acetone, rinsing with water or methanol resulted in retention … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
64
1
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(66 citation statements)
references
References 43 publications
0
64
1
1
Order By: Relevance
“…At low current density of 1 mA/cm 2 , the POM-Ppy/CC had a maximum areal capacitance of 561 mF/cm 2 . This result are much better than previously reported values from the Ppy-based electrode materials [24]. As the current density was increased to 30 mA/cm 2 , the areal capacitance of the POM-Ppy/CC decreased slightly; 561 mF/cm 2 ), respectively.…”
Section: Resultscontrasting
confidence: 51%
See 1 more Smart Citation
“…At low current density of 1 mA/cm 2 , the POM-Ppy/CC had a maximum areal capacitance of 561 mF/cm 2 . This result are much better than previously reported values from the Ppy-based electrode materials [24]. As the current density was increased to 30 mA/cm 2 , the areal capacitance of the POM-Ppy/CC decreased slightly; 561 mF/cm 2 ), respectively.…”
Section: Resultscontrasting
confidence: 51%
“…This study showed high specific capacitances of 120 F/g for POM-doped polyaniline [23]. Freund et al reported a higher specific capacitance (210 F/g) for pseudocapacitors based on porous structure of POM-doped polypyrrole electrodes [24]. The porous structure enabled efficient and rapid ion transfer, and thus improved electrochemical performances.…”
Section: Introductionmentioning
confidence: 56%
“…Porous nanostructures have received great attention because of their wide-ranging applications, such as in lithium-ion batteries [1][2][3], ion exchange membranes [4], catalysis supports [5][6][7][8], solar cells [9], and supercapacitor electrodes [10][11][12][13][14] due to their high surface area and enhanced interaction with the environment [15]. In the case of charge storage applications, transition metal oxide nanostructures are attractive candidates by virtue of their excellent pseudocapacitive behavior and high electrical conductivity [16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…[14][15][16][17][18][19] Recently, extensive research has been launched into the development of graphene-based composites for supercapacitor applications, especially for composites that consist of graphene and transition-metal oxides because they can combine the advantages of both components and may offer special properties through the reinforcement or modification of each other. [20,21] Several graphene/transition-metal oxide composites, such as graphene/MnO 2 , graphene/Mn 3 O 4 , graphene/ Bi 2 O 3 , graphene/Co 3 O 4 , and graphene/ZnO, [22][23][24] have been exploited and improved pseudocapacitor performances have been found in these composite systems. Nevertheless, all these investigations focused on composite powder materials, and there are few reports dedicated to graphene/transitionmetal oxide hybrid films.…”
Section: Introductionmentioning
confidence: 99%